2013
DOI: 10.1007/s00774-013-0459-4
|View full text |Cite
|
Sign up to set email alerts
|

Association between metabolic syndrome and bone mineral density in Korea: the Fourth Korea National Health and Nutrition Examination Survey (KNHANES IV), 2008

Abstract: Little is known regarding the exact relationship between osteoporosis and cardiovascular disease. Moreover, previous research on the relationships between components of metabolic syndrome (MetS) and bone mineral density (BMD) has primarily focused on women and older men; there have been few studies in younger men. We performed a cross-sectional study to assess whether MetS is associated with BMD in the femoral neck or lumbar spine in Korean adults. We further attempted to identify the MetS component, which is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
21
0
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 39 publications
3
21
0
1
Order By: Relevance
“…In another study involving Korean men aged 40 years or older and postmenopausal women, MetS was associated with a lower bone mineral density at the femoral neck [4]. Similarly, a negative relationship between bone mineral density and waist circumference was reported among Korean men after adjusting for age, weight, height, and lifestyle-related variables [5]. In contrast, a longitudinal study involving postmenopausal Korean women indicated that those with MetS had a lower annual decrease in bone mineral density compared with MetS-free women after adjusting for age, lifestyle, and baseline bone mineral density.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In another study involving Korean men aged 40 years or older and postmenopausal women, MetS was associated with a lower bone mineral density at the femoral neck [4]. Similarly, a negative relationship between bone mineral density and waist circumference was reported among Korean men after adjusting for age, weight, height, and lifestyle-related variables [5]. In contrast, a longitudinal study involving postmenopausal Korean women indicated that those with MetS had a lower annual decrease in bone mineral density compared with MetS-free women after adjusting for age, lifestyle, and baseline bone mineral density.…”
Section: Discussionmentioning
confidence: 83%
“…However, in population-based studies, the association between MetS and osteoporosis/ low bone mineral density has been controversial. Some studies have shown that MetS or its components are a detrimental factor [3][4][5]. In other studies, MetS was a beneficial factor before adjusting for weight and height or for body mass index [6][7][8][9] and was not a risk factor by gender [10].…”
Section: Introductionmentioning
confidence: 95%
“…Model 4 was adjusted for the covariates of model 3 and metabolic syndrome and periodontitis [6], which are known to be related to increased systemic inflammation [41]. Moreover, metabolic syndrome and periodontitis are associated with BMD in some studies [11][12][13]17]. The relationship between metabolic syndrome and BMD is controversial in men and women [42][43][44][45][46][47], but the results were mostly consistent in men.…”
Section: Discussionmentioning
confidence: 97%
“…The risk factors for the development of osteoporosis are old age, postmenopausal women, low calcium intake, low vitamin D level, and health behaviors such as smoking, alcohol intake, and physical activities [8][9][10]. Cardiometabolic abnormalities including dyslipidemia and metabolic syndrome are also known to be associated with the prevalence of osteoporosis [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 97%
“…Potential contributors include greater risk of falls, adverse changes on skeletal biomechanics, alterations in energy metabolism, metabolic syndrome, and overt type 2 diabetes mellitus or its associated treatments and comorbidities. (21)(22)(23)(24)(25) Of course, this assumes that the association between obesity and fractures is causal. But what if the association is not causal at all?…”
mentioning
confidence: 99%